2009
DOI: 10.1177/155005940904000307
|View full text |Cite
|
Sign up to set email alerts
|

Brain Electrical Responses to High- and Low-Ranking Buildings

Abstract: Since the ancient world, architecture generally distinguishes two categories of buildings with either high- or low-ranking design. High-ranking buildings are supposed to be more prominent and, therefore, more memorable. Here, we recorded event-related potentials (ERPs) to drawings of buildings with either high- or low-ranking architectural ornaments and found that ERP responses between 300 and 600 ms after stimulus presentation recorded over both frontal lobes were significantly more positive in amplitude to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…Compared with Oppenheim's work [1,3], our stimuli are pictures of natural scenes whereas theirs are hand-drawn pictures. Vessel and Rubin's [28] study found that observer agreement in preferences ratings for real-world images is higher than that for abstract images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with Oppenheim's work [1,3], our stimuli are pictures of natural scenes whereas theirs are hand-drawn pictures. Vessel and Rubin's [28] study found that observer agreement in preferences ratings for real-world images is higher than that for abstract images.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Oppenheim et al [3] carried out an event-related potentials (ERP) study, which discovered that high-ranking (classic) buildings elicited a lower N400 amplitude than low-ranking buildings. This finding indicated that neurophysiological correlates of building perception reflect an architectural rule system in the memory.…”
Section: Introductionmentioning
confidence: 98%
“…Most existing neuro-architectural studies are based on stationary protocols with participants focusing on visual stimuli while being seated or lying down to measure the subjective experience of architectural aesthetics. Investigating event-related potentials (ERP) of the EEG, Oppenheim et al (2009 , 2010) found that buildings that rank high regarding their social status as they are designed to be more important (like government buildings) or sublime (like religious buildings) have more impact on the perception of sublimity than low-ranking buildings (such as buildings associated with economy or the private life). In these studies, the hippocampus was shown to contribute to the processing of architectural ranking.…”
Section: Neuro-architecture Research Methods Findings and Limitationsmentioning
confidence: 99%
“…Frontal lobes with event-related potentials of higher positive amplitude, between 300 and 600 ms, when viewing architectural ornaments [553].Susceptible to cultural modulation [554].…”
Section: Contours and Ornamentsmentioning
confidence: 99%